2020
DOI: 10.1111/jfd.13249
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization of Polish isolates of infectious pancreatic necrosis virus in salmonid fish

Abstract: Infectious pancreatic necrosis virus (IPNV) is a virus belonging to the genus Aquabirnavirus and family Birnaviridae (Abdullah, Olsen, Hodneland, & Rimstad, 2015). The virus was first isolated in North America in 1960 and later was diagnosed in Europe and Japan. Now, it seems to be a significant and the most widespread virus in global freshwater aquaculture (Alonso, Rodriguez, & Perez-Prieto, 1999). The virus has been isolated from many fish species, crustacea and molluscs (Alonso, Rodriguez Saint-Jean, & Pere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…For instance, for the most critical positions associated with the virulence, i.e., 217 and 221 of the VP2, the amino acid residues of our assembled genomes are proline (P) and threonine (T) (Table 1; Supplementary File S1), while it is expected that in the virulent form, the corresponding residues to be T and A, respectively (Santi et al, 2004;Song et al, 2005;Mutoloki et al, 2016). Similar patterns have also been reported from the isolates recovered from outbreaks, with the amino acid signature comparable to the non-virulent forms in the key positions (Bain et al, 2008;Maj-Paluch et al, 2020;Ruane et al, 2009, Ruane et al, 2015Tapia et al, 2015). On the other hand, we identified ten amino acid residues in the assembled genomes' polyprotein that are either exclusively or with a disproportionate frequency in the reported isolates (Table 2; Supplementary File S1).…”
Section: Frontiers Insupporting
confidence: 68%
See 1 more Smart Citation
“…For instance, for the most critical positions associated with the virulence, i.e., 217 and 221 of the VP2, the amino acid residues of our assembled genomes are proline (P) and threonine (T) (Table 1; Supplementary File S1), while it is expected that in the virulent form, the corresponding residues to be T and A, respectively (Santi et al, 2004;Song et al, 2005;Mutoloki et al, 2016). Similar patterns have also been reported from the isolates recovered from outbreaks, with the amino acid signature comparable to the non-virulent forms in the key positions (Bain et al, 2008;Maj-Paluch et al, 2020;Ruane et al, 2009, Ruane et al, 2015Tapia et al, 2015). On the other hand, we identified ten amino acid residues in the assembled genomes' polyprotein that are either exclusively or with a disproportionate frequency in the reported isolates (Table 2; Supplementary File S1).…”
Section: Frontiers Insupporting
confidence: 68%
“…Further, assessment of the recombinant viral strains has indicated that a threonine (T) residue rather than proline (P) in position 217 of the VP2 might be the most crucial amino acid that can result in the loss or gain of virulence (e.g., Song et al, 2005). Nonetheless, there has also been evidence from field outbreaks and challenge experiments that IPNV variants with a P substitute in this position can lead to high mortalities (Bain et al, 2008;Ruane et al, 2009Ruane et al, , 2015Tapia et al, 2015;Maj-Paluch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Primers were designed by using Primer3Plus software [ 9 ], as follows: for VHS [ 10 ], for IHN [ 11 ] and for IPN [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…27 Since then, most isolates identified in Europe belong to Genogroup 5. They are found in almost all salmon-producing countries in Europe and, according to molecular analysis, this genogroup is the only one reported in some countries including Croatia, [57][58][59] Bosnia and Herzegovina, 59 France, 27,60 Italy, 49 Ukraine, 61 Turkey, [62][63][64] Poland, 65 and Norway. [66][67][68][69][70][71] In Norway, the largest Atlantic salmon worldwide producer, IPNV was isolated for the first time in 1975 from rainbow trout.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%